The Effect of e-WOM, Neutral-Third Party Source, and Manufacturer or Retailer Source as Online Information Sources toward Purchase Intention with the Mediation of Brand Attitude on Nature Republic - Jesslyn Ivana Joviaal; Melinda Tasya Halim (iBuss Management, 2020)
Internet has always been regarded as a reliable tool for information sharing. Huge number of people are using it as a platform of online information sources. Along with the emergence of beauty and cosmetic industries, consumers also need to rely more on online information sources given its ability has enable customers to make more informed choices in a purchase decision. Thus, the purpose of this research is to examine the effect of online information sources, namely, e- WOM, neutral-third party sources, and manufacturer or retailer sources in i fl e ci g c e cha e i e i i h he edia i f b a d a i de Nature Republic as one of the top six favourites cosmetics brand in Indonesia. A sample size of 110 respondents living in Java Island was gathered and used during the research. The data is further analysed using path analysis via multiple linear regression, using two regression models as well as the Sobel test to further measure the mediation relationship between variables. Furthermore, the result of the research shows that online information sources, namely, e-WOM, neutral-third party sources, and manufacturer or retailer sources does significantly affects purchase intention through the mediation of brand attitude.Keywords: Electronic Word of Mouth/e-WOM, Neutral-Third Party Source,Manufacturer or Retailer Source, Brand Attitude, Purchase Intention